2021
DOI: 10.1016/j.jbc.2021.100679
|View full text |Cite
|
Sign up to set email alerts
|

A versatile cis-prenyltransferase from Methanosarcina mazei catalyzes both C- and O-prenylations

Abstract: Polyprenyl groups, products of isoprenoid metabolism, are utilized in peptidoglycan biosynthesis, protein N -glycosylation, and other processes. These groups are formed by cis -prenyltransferases, which use allylic prenyl pyrophosphates as prenyl-donors to catalyze the C -prenylation of the general acceptor substrate, isopentenyl pyrophosphate. Repetition of this reaction forms ( Z,E -mixed)-polyprenyl pyrophosphates, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Instead, the cPTL family that functions as a regulatory subunit of L‐cPT contains an RXG motif, although in some cases the first Arg residue in this motif is substituted with Asn. Similar substitutions from the conserved Arg to Asn residues have been observed in the C‐terminal regions of archaeal M‐cPTs [15] . The crystal structure of ( Z,Z )‐FPP (C 15 ) synthase (zFPS), an S‐cPT from wild tomato, revealed that the RXG motif interacts with IPP near the S2 site, although the crystal structure was solved as an unusual complex that binds the IPP‐Mg 2+ ‐IPP complex at the active site [16] .…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Instead, the cPTL family that functions as a regulatory subunit of L‐cPT contains an RXG motif, although in some cases the first Arg residue in this motif is substituted with Asn. Similar substitutions from the conserved Arg to Asn residues have been observed in the C‐terminal regions of archaeal M‐cPTs [15] . The crystal structure of ( Z,Z )‐FPP (C 15 ) synthase (zFPS), an S‐cPT from wild tomato, revealed that the RXG motif interacts with IPP near the S2 site, although the crystal structure was solved as an unusual complex that binds the IPP‐Mg 2+ ‐IPP complex at the active site [16] .…”
Section: Introductionsupporting
confidence: 72%
“…Similar substitutions from the conserved Arg to Asn residues have been observed in the C-terminal regions of archaeal M-cPTs. [15] The crystal structure of (Z,Z)-FPP (C 15 ) synthase (zFPS), an S-cPT from wild tomato, revealed that the RXG motif interacts with IPP near the S2 site, although the crystal structure was solved as an unusual complex that binds the IPP-Mg 2 + -IPP complex at the active site. [16] A mutagenesis study in the same report indicated that mutations in the RXG motif resulted in a significant loss of condensation activity in zFPS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MA1831 from Methanosarcina acetivorans and MM0014 from Methanosarcina mazei are UPPS orthologs, but their functions differ from UPPS, and both of them do not possess the common C‐terminal RXG motif (Figure 7). MA1831 could catalyze non‐canonical head‐to‐middle condensation and produce C35–C50 products, while MM0014 could yield C25–C40 products and have O‐prenyltransferase activity (Ogawa et al, 2016; Okada et al, 2021). Besides, the heteromeric cis‐PT homologues from Archaeoglobus fulgidus , a thermophilic archaeon, were recently biochemically characterized (Sompiyachoke et al, 2022).…”
Section: Resultsmentioning
confidence: 99%